Penerapan Metode Diskusi untuk Meningkatkan Keaktifan dan Hasil Belajar PKn pada Siswa Kelas II.D SD Negeri 64/IV Kota Jambi - Ely Afrida (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Research is backed by the interview and evaluation of the implementation of PKN-learning in class II. D SD Negeri 64/IV Jambi City years lesson 2016/2017 obtained the following data: (1) Learning activities are still dominated by the teachers so that students are less active to follow PKn-learning, (2) methods used in learning PKN- To the planting of information/concepts learned to be notified or presented with a lecture only; (3) in the process of learning PKN students feel less guidance and tutoring in self-study, (4) In learning teachers still apply dictated in the recording of the learning material of PKn. Research objectives for Improve the activity and learning outcomes of PKn through the method of discussion in class II students. D SD Negeri 64/IV Jambi City in lesson year 2016/2017. The questions that want to be answered in the study are 1) whether the implementation of the method of discussion can improve the active learning of PKN in students grade II. D SD Negeri 64/IV Jambi City odd semester year 2016/2017? 2) Whether the implementation of a method of discussion can improve the active learning of PKN in grade II students. D SD Negeri 64/IV Jambi Odd semester year lesson 2016/2017? To answer the question, this research uses class action research (PTK). The data collection techniques in this study use observations, documentation, and tests to measure student learning outcomes. The subject of this study is all grade II students. D SD Negeri 64/IV Jambi City years lesson 2016/2017 as many as 36 students. It can be seen from the research results in grade II students. D SD Negeri 64/IV Jambi City, that is, in the cycle I, the results of learning management reached 63.39% and students ' study activity reached 74.39% and the learning outcomes were 65.00. In the II cycle of teacher learning management reached 91.07% and student learning activity reached 84.42% and students ' learning outcomes were multigrade by the average rating of 83.91. Furthermore, the higher the student's management and learning activities will increase students ' learning.